Os Black Stars Chegam Ao Mercado: O Jogador Ganês Na Geopolítica Das Relações Internacionais Entre Inglaterra E Gana No Pós Colonialismo (1996-2014) - Portela, Jonathan Dias [UNIFESP] (2018)
This Master's Thesis Aims To Analyze The Trajectory Of Ghanaian Athletes Inserted In English Football Between 1996 And 2014, Under The British Press Sighr. In This Way, It Is Sought To Reflect On The Neocolonial Discourse Through Sport, Especially In What Concerns The Constructions Of The Hierarchizations Of The Players From The Old African Colonies, In View Of The English Sport Context And The Geopolitical Perspective Of Contemporary England In Their Relations With The African Areas Of The Former Colonial Empire.